Carbon Sequestration of mangrove forest in Delta Tumpat, Kelantan - Risyon, Nadia Shavika (2018)
Mangrove plantation is expected to be one of the afforestation forests as a Clean Development Mechanism (CDM) project. Mangrove ecosystem accumulates sequestered carbon in sediment compared to the land forest. The carbon emission that produced by the human activities will be captured and divert them from reaching the atmosphere to secure storage. The potential carbon value of a healthy mangrove forests are according to carbon store and for carbon sequestration. A study was conducted at Delta Tumpat, Kelantan to estimate the carbon sequestration and to determine the appropriate allometric equations for aboveground biomass of mangrove forest at Pulau Bedal A, Pulau Bedal B, Pulau Mas, Pulau Tujuh and Pulau Layang-layang. A total of 491 individuals of Rhizophora apiculata and Rhizophora mucronata were identified. Aboveground biomass (AGB) was calculated by following Komiyama (2015) where the value is 67.04 tan /ha. Meanwhile, the carbon stock estimated is 32.85 tan C/ha with taking into account that the value of carbon stock is 49% of aboveground biomass. The carbon sequestration in the study area is 2.23 tan C/ha/year. It is consider high because of the forest is filled with young trees and still consider as young forest with the oldest tree ages only 17 years old. Thus, the young-growth forest can store enormous amount of carbon. The diameter breast height (DBH) and height must in a high value in order to sequester carbon in the higher amount. The appropriate allometric equation is equation that developed by Komiyama et al.,(2005). This equation gave an accurate value of AGB and the average error was within 10%. Futher study should be done in the area to add up more of data and knowledge about Delta Tumpat vegetation. This will also helped the related department in managing and conserving the area for its importance purposes.